"Potencial de fungos filamentosos para promoção de crescimento vegetal sob condições de déficit hídrico. " - SAMANTA MONÇÃO SILVA (2025)
The global average temperature has increased between 0.2 °C and 1.1 °C since 1850, a period associated with the Industrial Revolution. This variation, driven by climate change, has a significant impact on agriculture, intensifying abiotic stress. In this context, endophytic fungi have stood out for establishing mutualistic relationships with plants, providing benefits such as increased tolerance to abiotic stress. This study aimed to identify new drought-tolerant fungal isolates and evaluate their potential as plant growth promoters. The isolates were collected from rocky outcrops at Fazenda São João (Corumbá/MS), obtained from the roots of *Discocactus ferricola*. Fungal growth tests were conducted at different temperatures (30 °C, 35 °C, and 40 °C) and under water deficit conditions using PEG (-0.1 MPa, -0.2 MPa, and -0.4 MPa). After defining the parameters, the isolates were assessed for plant growth promotion, with and without PEG (-0.1 MPa). The analyzed fungi included *Penicillium* sp. (DF1 and DF5), *Aspergillus* sp. (DF2 and DF4), *Chaetomium* sp. (DF3), and *Trichoderma* sp. (T24 and GT31). All isolates grew at 30 °C and 35 °C and showed growth in BD medium with -0.1 MPa of PEG. Among the isolates, DF1 stood out for its ability to solubilize calcium and aluminum phosphates, both in the presence and absence of PEG. All isolates produced ACC deaminase (ACCD), with variations ranging from 18.46 ± 3.8 to 5.42 ± 2.4 μM of α-ketobutyrate h⁻¹ mg⁻¹ protein. Indole-3-acetic acid (IAA) production was observed in all tested fungi, with DF2 showing the highest concentration in the presence of PEG (53.99 ± 0.6 μg/mL). Regarding siderophore production, all isolates maintained consistent production, with DF1 exhibiting the highest values in both normal medium and PEG (-0.1 MPa). Enzymatic assays demonstrated that the isolates produce crucial enzymes for the carbon cycle. DF1 (*Penicillium* sp.) was selected for maize experiments conducted in a greenhouse under water stress conditions due to its relevant characteristics, including IAA production, siderophore synthesis, phosphate solubilization, ACC deaminase activity, and enzymes associated with nutrient cycling. Our results showed that DF1 contributed to plant defense strategies under water deficit conditions, promoting the accumulation of osmolytes such as total sugars, reducing sugars, and free amino acids for tissue protection and stimulating the production of antioxidant enzymes essential for mitigating damage caused by reactive oxygen species (ROS). Additionally, DF1 increased microbial activity in the soil, contributing to environmental health and fertility, as well as a more balanced nutrient cycle. Based on these findings, fungal isolates from predominantly rocky regions demonstrated significant potential in promoting plant growth under water stress conditions.